2022
DOI: 10.12911/22998993/144691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Charging and Discharging Process of PCM with Paraffin and Al<sub>2</sub>O<sub>3</sub> Additive Subjected to Three Point Temperature Locations

Abstract: This analysis focused on investigating thermal storage behaviour on phase change material along with Al 2 O 3 as an additive. The experimental investigation was performed by three set temperature points, i.e. 40 °C, 50 °C and 60 °C with the mass circulation rate through the tank of 5 kg/min, 3 kg/min and 2 kg/min. The forced circulation method was used to circulate the liquid, water was used as a working medium and Al 2 O 3 as nano particle. Paraffin acts a phase change material to conduct the experimental pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Because of the load increases, the surface tensions offered by the fuel are also reduced, and this causes the lower induction of mass of the working fluids and air to lower the volumetric efficiency compared to 25% load conditions. 80 At full load conditions, 100% of the maximum volumetric efficiency is obtained for the fuel diesel and the D70RP21B9. Because the D70RP21B9 blend causes a higher oxidation capacity, the MFB attainments at the peak level cause attainment of the maximum volumetric range of 82%; but for the diesel fuel, the volumetric efficiency of up to 80% is achieved.…”
Section: Combustion Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Because of the load increases, the surface tensions offered by the fuel are also reduced, and this causes the lower induction of mass of the working fluids and air to lower the volumetric efficiency compared to 25% load conditions. 80 At full load conditions, 100% of the maximum volumetric efficiency is obtained for the fuel diesel and the D70RP21B9. Because the D70RP21B9 blend causes a higher oxidation capacity, the MFB attainments at the peak level cause attainment of the maximum volumetric range of 82%; but for the diesel fuel, the volumetric efficiency of up to 80% is achieved.…”
Section: Combustion Characteristicsmentioning
confidence: 98%
“…At load, it gradually increased from 25 to 50%; this efficiency significantly decreased for the diesel and royal poinciana blends. Because of the load increases, the surface tensions offered by the fuel are also reduced, and this causes the lower induction of mass of the working fluids and air to lower the volumetric efficiency compared to 25% load conditions . At full load conditions, 100% of the maximum volumetric efficiency is obtained for the fuel diesel and the D70RP21B9.…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…[ 27 ] Effectively managing charging and discharging rates is crucial for regulating battery temperature. [ 28 ] Table 2 shows the maximum surface temperatures developed in the desired charge and discharge rates.…”
Section: Factors and Challenges In Battery Thermal Management Systemmentioning
confidence: 99%
“…Most advanced techniques with latest sensors must need to employ to found fault diagnosis techniques, to prevent or minimize the downtime of the turbine. It was found that downtime maintanence of wind turbine gearbox has been rapidly decreased in the states due to latest and advanced technologies has been adopted, hence it was required to adopt those technologies in india, According to Nie et al [4] and Kumar et al [5], Fault tree analysis is the root cause method to identify the possible occurance of the failure to be occurred while the gearbox is running at very higher speeds, and the information also predicts may provides the maximum possible failures of gearbox parts such as bearings and higher speed fastners, bolts subjected to higher elevated temperatures proved by Zhi-Ling et al [6]. The major downtime of the gearbox may occur due to the improper or poor maintanence of temperature, pressure and health monitoring sensors, leads to uncontrol the debris particle of oil resulted in increasing the down time of the wind turbine power plant represented by Feng et al [7].…”
Section: Introductionmentioning
confidence: 99%